Pattern and treatment of Gout in Bangladesh: a hospital based survey at Dhaka city, Bangladesh - Most. Nazma Parvin, Sadia Afreen Chowdhury, S.M. Ashraful Islam, Riaz Uddin (Journal of Applied Pharmaceutical Science)
Gout is a common metabolic disorder which occurs due to excessive deposition of uric acid in different bone joints. Increasing life expectancy, life style change, changes in diet are causing an increased incidence of the disease nowadays. The present study was aimed to understand the pattern and treatment of gout in Bangladesh. 150 patients at four tertiary care hospitals in Dhaka city were surveyed. The findings of the present study suggests that both male and female are suffering from the disease and age seems to be related to the disease as 62% of gout patients were found over 50 years of age. Body weight may be a contributing factor of the disease. Most of the gout patients under the survey were suffering from high blood pressure (65.33%). Primary gout was found more prevalent in this investigation (70.66%) and viral hepatitis was found to be the most common cause of the disease (50%). The patients presented common sign and symptoms of gout.
Keywords: Metabolic disorder, uric acid, obesity, steroid injection, dislocated bone